Network disruption detected in MZ (Mozambique) - Voidly (2026)
CRITICAL severity disruption detected in Mozambique. Confidence: 70%. Data sourced from IODA.
Network Disruption Incident ID: MZ-2026-0001
Keywords: internet disruption; MZ; disruption; critical